Leishmania martiniquensis is a New Causative Agent for Cutaneous and Visceral Leishmaniasis in Humans - S. B. Chuelov; A. L. Rossina (LLC "Diagnostics and Vaccines", 2018)
The article contains a literature review devoted to the history of the study of human leishmaniasis and one of the new pathogens - Leishmania martiniquensis. It is shown that leishmaniasis caused by this microorganism proceeds in the form of cutaneous, including diffuse in HIV-infected patients, and visceral leishmaniasis. The most typical clinical examples are given.